Immediate effects of rhythmic joint mobilization of the temporomandibular joint on pain, mouth opening and electromyographic activity in patients with temporomandibular disorders. (October 2021) - Barone, M.; Imaz, F.; Converso, G.; Bordachar, D.; Barbero, A.; Trucco, M.; Intelangelo, L.
Abstract: Background: Rhythmic joint mobilizations (RJM) of the temporomandibular joint (TMJ) are employed to relieve pain and improve function in patients with temporomandibular disorders (TMD). However, the evidence on the immediate effects of RJM in patients with TMD is scarce. The aim of this study was to assess the immediate clinical and functional effects of RJM in patients with TMD. Materials and methods: This was a one-group quasi-experimental before and after study. Thirty-eight patients with TMD were assessed by means of pain intensity (visual analogue score, VAS), pressure pain threshold (PPT, measured through pressure algometry on the masseter and temporal muscles), mouth opening (MO, measured with a ruler), and surface electromyographic activity of the masseter and temporal muscles (asymmetry index, AI). Measurements were performed before and after a single, 1-min session of RJM of each TMJ. All statistical analyses were performed using the SPSS version 20.0 statistical package. Results: A statistical significant difference was found in pain intensity, PPT and MO after the intervention (p < 0.05). No difference was found in the AI. A large effect size was observed for pain intensity, PPT of the left and right masseter muscles and MO (d = 0.85–1.13), whereas for the left and right temporal muscles the effect size was moderate (d = 0.62) and small, respectively (d = 0.49). Conclusion: In this sample of patients with TMD, a single session of RJM of the TMJ seemed to be effective in reducing pain intensity, increasing PPT and improving MO immediately after the intervention, without differences in the AI.